Self-perception, body satisfaction and cohesion in high performance gymnasts from a private school in the city of Temuco (Revista horizonte, 2011)
Self-perception, body satisfaction, and social cohesion are investigated in a group of high performance gymnast girls, belonging to a private school in the city of Temuco, Chile. The research method is a mixed methodology of qualitative predominance of the transectional exploratory type. The total sample consisted of 19 girls, between 8 and 13 years old, members of a high performance rhythmic gymnastics team. The instrument developed by Cooper, Taylor, Cooper and Fairburn (1987), Body Shape Questionnaire, was used, in addition to a sociogram, to know the state of cohesion of the group, and a projective test, to know the body self-perception. As main result, some cases of body dissatisfaction, self-perceptive distortion and low group cohesion were found. As main conclusion, it is possible to affirm that this study is in line with others developed at international level, where sports that emphasize physical aesthetics as an important element, tend to generate body dissatisfaction and self-perceptive distortion.